Management аccounting: What is subject to digital transformation? - O. E. Mikhnenko; V. N. Salin (Управленческие науки, 2022)
The subject of the article are the problems of transformation on the basis of breakthrough digital technologies of activity on information support of management and use of accounting information in managerial decision-making. The authors in the course of the research analyze the current state of management accounting and prove that only a factor information model is able to ensure the implementation of the functions of the actual management of the object, allowing observation based on operational, technical, accounting, statistical and data integration requirements. On the example of the system of productivity indicators (qualitatively defined quantity), it is demonstrated that it is possible to implement such requirements for this factor as the object, accuracy and specificity of the work; and an example of a system of indicators for fixed assets — harmonies the functions performed for the object. The article also substantiates the conclusion that the solution of the problems of digital transformation of speech can be provided by an information system functioning based on the platform using Big Data and cloud technologies — DaaS interacting with active elements of the Internet community. In the course of the study, in generalization of modern concepts of management of economic systems, directions of development of digital technologies and their implementation in the processes of information management, methods of system and comparative analysis were used.